2001
DOI: 10.1093/hmg/10.19.2079
|View full text |Cite
|
Sign up to set email alerts
|

Defective satellite cells in congenital myotonic dystrophy

Abstract: In this study we have developed an in vitro cell culture system which displays the majority of the defects previously described for congenital myotonic dystrophy (CDM) muscle in vivo. Human satellite cells were isolated from the quadriceps muscles of three CDM fetuses with different clinical severity. By Southern blot analysis all three cultures were found to have approximately 2300 CTG repeats. This CTG expansion was found to progressively increase in size during the proliferative life span, confirming an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 47 publications
10
93
2
1
Order By: Relevance
“…Therefore, it seems that proliferation and differentiation are intrinsic features of the individual samples, and are not correlated with their disease status. In this respect, the HIBM primary myoblast cultures differ from those derived from myotonic dystrophy and HD patients, 18 that showed lower differentiation index than controls, and from congenital myotonic dystrophy (CMD), 19 and Duchenne muscular dystrophy (DMD) cells, 20,21 in which both proliferation and differentiation abilities are damaged. Thus, in these pathologies, basic biological functions of muscle satellite cells in culture are impaired.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it seems that proliferation and differentiation are intrinsic features of the individual samples, and are not correlated with their disease status. In this respect, the HIBM primary myoblast cultures differ from those derived from myotonic dystrophy and HD patients, 18 that showed lower differentiation index than controls, and from congenital myotonic dystrophy (CMD), 19 and Duchenne muscular dystrophy (DMD) cells, 20,21 in which both proliferation and differentiation abilities are damaged. Thus, in these pathologies, basic biological functions of muscle satellite cells in culture are impaired.…”
Section: Discussionmentioning
confidence: 98%
“…The changes in apoptotic processes seen in HIBM satellite cells might be one of the initial pathologic events leading to the degeneration of muscle tissue, since they appear during the mitotic phase, while other biological functions of the cells -morphology, proliferation, senescence and differentiation -seem normal. In contrast, in highly degenerative diseases such as HD, CMD and DMD, most basic biological functions are impaired from the early stages of satellite cells activation, 17,19,21 and therefore even when apoptotic processes are involved, it is difficult to point to the initial steps of the process. Presently, the upstream events in HIBM pathophysiology, in terms of intracellular and intercellular signaling, have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…52 The proliferative ability of FSHD myoblasts was also explored by the measurement of the telomere size. The length of the telomeric DNA is an indicator of cell proliferation, its measurement reflects the past divisions and is related to the remaining proliferation ability.…”
Section: Discussionmentioning
confidence: 99%
“…25,32 Here we showed that retrovirus producing (CUG) 13 antisense RNA has no effect on the proliferative rate of DM1 myoblasts; however, it restores the differentiation of infected DM1 myoblasts as indicated by the increase in the fusion index, in the mean number of nuclei per myotube as well as in the uptake of glucose. The specificity of these effects is supported by the fact that two other retrovirus producing the GFP protein or an antisense RNA against the 5 0 UTR have no effect on the levels of DMPK mRNAs nor on the growth and differentiation of DM1 myoblasts.…”
Section: Targeting Of Mutant Dmpk Transcripts D Furling Et Almentioning
confidence: 94%
“…The recovery of RNAs was determined by hybridization with a 32 Plabeled cyclophilin DNA probe as described. 32 DMPK probe was generated by random priming of 25-50 ng of the DMPK cDNA (BglII-SacI fragment) and hybridization was done overnight at 681C in hybridization buffer (2% SDS/10% dextran sulfate/1 Â SSPE/10 mg/ml salmon sperm DNA/2% Denhart's). Quantitation of relative RNA levels of autoradiograms was determined by densitometry (AlphaImager scan from Alpha Innovatech Corp.).…”
Section: Northern Blot Analysismentioning
confidence: 99%